2020
DOI: 10.3389/fcell.2020.00529
|View full text |Cite
|
Sign up to set email alerts
|

USP15 Enhances Re-epithelialization Through Deubiquitinating EIF4A1 During Cutaneous Wound Repair

Abstract: Re-epithelialization is a fundamental process in wound healing that involves various cytokines and cells during cutaneous barrier reconstruction. Ubiquitin-specific peptidase 15 ( USP15 ), an important member of the deubiquitinating enzymes (DUBs), removes ubiquitin chains from target proteins and maintains protein stability. However, the dynamic role of USP15 in epithelialization remains unclear. We aimed to investigate the regulatory function of USP15 in re-epithelialization. An excisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
(36 reference statements)
1
8
0
Order By: Relevance
“…In prior studies, USP15 was shown to interact with EIF4A1 and to thereby accelerate wound healing [ 33 ]. Consistent with such a model, we found that USP15 knockdown was sufficient to reduce EIF4A1 expression, while EIF4A1 knockdown directly impaired HaCaT cell migration and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In prior studies, USP15 was shown to interact with EIF4A1 and to thereby accelerate wound healing [ 33 ]. Consistent with such a model, we found that USP15 knockdown was sufficient to reduce EIF4A1 expression, while EIF4A1 knockdown directly impaired HaCaT cell migration and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In prior studies, USP15 was shown to interact with EIF4A1 and to thereby accelerate wound healing. 30 Consistent with such a model, we found that USP15 knockdown was su cient to reduce EIF4A1 expression, while EIF4A1 knockdown directly impaired HaCaT cell migration and proliferation. Together, these results suggest that the USP15-EIF4A1 axis is a key mediator of the re-epithelialization process.…”
Section: Discussionsupporting
confidence: 78%
“…Consistent with the in vivo or in vitro measurements, we observed that USP15 stimulated the TGF-β signaling pathway through p-SMAD2 and inhibited OA progression by increasing Col2a1, Aggrecan, and Sox9 levels and suppressing Col10a1 and MMP13 levels. According to these reports, USP15 played indispensable roles in many diseases such as safeguarding genome integrity in leukemia cells, promoting the apoptosis of degenerative nucleus pulposus cells, and enhancing re-epithelialization through deubiquitinating EIF4A1 during cutaneous wound repair [40][41][42]. However, there are few previous studies on the effects of USP15 on OA.…”
Section: Discussionmentioning
confidence: 99%